Clinical, electroanatomic and electrophysiologic characterization and outcomes of catheter ablation for ventricular tachycardia following valvular intervention. (8th February 2022) - Bennett, Richard G.; Garikapati, Kartheek; Anderson, Robert D.; Silva, Kasun De; Campbell, Timothy; Kotake, Yasuhito; Turnbull, Samual; Tonchev, Ivaylo; Lee, Geoffrey; Kalman, Jonathan; Kumar, Saurabh
Abstract: Introduction: Ventricular tachycardia (VT) can occur following valvular interventions. There are limited data describing substrate and ablation approaches in such patients. We sought to describe the clinical, electrophysiologic, electroanatomic features and catheter ablation outcomes of patients with VT following aortic and/or mitral valve intervention. Methods: Over 12‐years, consecutive patients with aortic valve replacement (AVR) and/or mitral valve replacement (MVR) or repair, undergoing VT ablation, were identified from two centers. Clinical and procedural parameters and outcomes are described. Results: Twenty‐three patients (age 66 ± 14years, 78% male, left ventricular ejection fraction 37 ± 16%), with prior AVR (mechanical n = 6, bioprosthetic n = 2, transcatheter n = 1), MVR (mechanical n = 5, bioprosthetic n = 1), mitral valve repair ( n = 6) and both mechanical AVR and MVR ( n = 2), underwent VT ablation. Sixteen had concurrent ischemic cardiomyopathy, 10 with prior bypass surgery. Left ventricular access was obtained in 21/23 (91%) patients (transseptal n = 14, retrograde aortic n = 5, transapical n = 2), with perivalvular scar identified in 17/21 (81%). Re‐entrant VT isthmi involved the perivalvular regions in 12/23 (52%) patients, and regions remote from the valve in the remainder; 9% had nonscar‐related VT. Intramural substrate was ablated from adjacent chambers in 5/23 (22%) patients and with half‐normal saline irrigation in 8/23 (35%) patients. There were no instances of catheter entrapment. Following final ablation, VA‐free survival was 78% at 13‐months. Conclusion: Only half of VT circuits following valvular interventions involve the valve regions themselves, while the remainder involves unrelated regions. Catheter ablation is safe and efficacious at treating VT following valvular intervention, but novel strategies may be required.